Recomendaciones para el apoyo psicológico a jóvenes deportistas en los centros de alto rendimiento - Rial, A.; Marsillas, S.; Isorna, M.; Louro, A. (Revista Internacional de Ciencias del Deporte, 2013)
In the context of sport, high performance became in one of the topics that has raised most interest in literature and has generated a great demand in applied level. Following the evidence, sports organizations and institutions have defined recruitment and training strategies for young athletes, allocating financial, human and material resources in order to maximize their potential. Today, much of these centers have multidisciplinary teams with different types of professionals: from trainers, doctors, nutritionists, retrievers, to sport psychologists. Indeed monitoring the psychological aspects related to high performance has gained a special importance in recent years. In this paper, the assessment to 57 young residents in the Sports Technifying Center of Pontevedra has allowed to identify some keys to provide adequate psychological support to athletes in training. Moreover, the information obtained is translated into recommendations that facilitate the daily work of the coaches and contributes to greater optimization of the resources invested.